Practical robotics and mechatronics marine, space and medical applications - Yamamoto, Ikuo (The Institute of Engineering and Technology, 2016)
"The world is experiencing the beginning of a revolution in robotics and mechatronics. A key part of this revolution is integration with the Internet of Things and machine-to-machine interfaces. This networking of robotics and mechatronics promises significant market opportunities for a new generation of robots. The basic theory and procedures for the design and development of practical robotics and mechatronics are important for all students and engineers who wish to engage in the field and this book provides an essential introduction to this, describing how to successfully create practical robotics and mechatronics. It is based on the author's 30 years of experience of robotics development in Mitsubishi Heavy Industries, Ltd., JAMSTEC, and Nagasaki University, and contains many examples of real-world robots from new underwater vehicles, ships, robotic fish, unmanned aviation robotics, to space robotics, and medical robotics"--Provided by publisher.